2013
DOI: 10.4028/www.scientific.net/amr.702.172
|View full text |Cite
|
Sign up to set email alerts
|

BiVO<sub>4</sub>-TiO<sub>2</sub> Nanocomposite: Synthesis and Photocatalytic Investigation

Abstract: BiVO4composited with TiO2(BVO-T) nanoparticles was sensitized by tetrakis(4-carboxy phenyl)porphyrin (TCPP) dye (BVO-T/P) to efficiently utilize visible light in the photodegradation reaction. To investigate the photoactivity of this catalyst, its photocatalytic efficiency was compared to the pure TiO2, pure BiVO4, and BiVO4composited with TiO2in the destruction of methyl orange in the visible light. Furthermore, the kinetic of the MO degradation as well as the stability of BVO-T/P photocatalyst was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This behaviour was attributed to the low activity of BiVO 4 derived from its small specific surface area, 52, 56 and 44 m 2 /g for nanocomposites ratios 1:10, 1:2.5 and 1:0.6 respectively. This morphology influences the density of photogenerated charge carriers 46 due to the recombination process. The ratio 1:10 was selected to conduct the dye removal by photocatalytic reactions since this compound showed the best results with the lowest concentration of the nanocomposite material.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour was attributed to the low activity of BiVO 4 derived from its small specific surface area, 52, 56 and 44 m 2 /g for nanocomposites ratios 1:10, 1:2.5 and 1:0.6 respectively. This morphology influences the density of photogenerated charge carriers 46 due to the recombination process. The ratio 1:10 was selected to conduct the dye removal by photocatalytic reactions since this compound showed the best results with the lowest concentration of the nanocomposite material.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of BiVO 4 and TiO 2 has attracted much attention recently in photocatalysis. 20,[24][25][26][27][28][29][30][31] However, the photocatalysis promoting mechanism remains unclear and diverging. Hu et al 26 proposed a band conguration where the CB and VB of BiVO 4 were positioned at locations higher than the CB and VB of pure TiO 2 , respectively.…”
Section: Photocatalysis Mechanismmentioning
confidence: 99%
“…22,23 The combination of a narrow bandgap semiconductor material such as BiVO 4 with TiO 2 to produce a BiVO 4 /TiO 2 nanocomposite with an intimate heterojunction could be an efficient way to offer a visible light photocatalyst with high photocatalytic activity and attracts increasing attention. 20,[24][25][26][27][28][29][30] Cao et al 24 synthesized the porous peanut-like BiVO 4 /TiO 2 composite nanostructures by a hydrothermal process and the photocatalytic activity of these BiVO 4 / TiO 2 nanostructures was largely enhanced. Zhang et al 25 reported the synthesis of BiVO 4 /TiO 2 by a one-step microwave hydrothermal method and found that the 20 wt% TiO 2 /BiVO 4 nanocomposite exhibited better photocatalytic activity than pure monoclinic BiVO 4 and other percentages of TiO 2 in BiVO 4 because of its high crystallinity, narrow bandgap, and most importantly, the hierarchical heterostructure which can effectively separate photoinduced electron-hole pairs on the surface of BiVO 4 /TiO 2 photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The well-matched energy band alignement is a key factor for the achievement of efficient heterojunctions [24,25]. Recently the BiVO 4 /TiO 2 heterojunction has been attracted considerable attention as a promising photocatalyst under visible light irradiation and has shown a significant suppression of the photogenerated electron-hole recombination [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%